Towards an Authentic Interpretation of Mendelssohn's Organ Works - Gates, Murray Eugene (My University, 1985)
A steady decline in the quality of organ literature began around the time of J. S. Bach's death (1750) , and continued into the early decades o f the nineteenth century. Through the publication of his Three Preludes and Fugues, Op. 37 (1837) and the Six Sonatas, Op. 65 (1845), Mendelssohn brought an end to the most decadent period in the history of German organ music. It may justly be said that he founded the modern school of organ composition.
Performers, teachers and critics frequently approach Mendelssohn's organ works from the perspective of the late nineteenth-century "symphonie" tradition, thus presenting a complete distortion of the composer's intentions. It is the purpose of this thesis to establish an historically accurate performance practice for Mendelssohn's important and unique contribution to the organ repertoire.
Many sources and documents from the period are available. Mendelssohn's performing career as a virtuoso organist (an area largely ignored by his biographers and music historians) is documented in his own letters and contemporary critique s of his concerts. These sources preserve considerable information on the subject of Mendelssohn's organ playing. It has been possible, through a study of the instruments on which he is known to have played, together with research into contemporary treatises on performance practice and organ building, to establish guidelines for a valid and accurate approach to the performance of Mendelssohn's organ works. Using these guidelines as criteria for evaluation, all presently available performing editions and recordings of his organ works have been critically examined from the perspective of historical accuracy.
Keywords: Music Criticsm; Music; Music